'The Pied Piper Has Played His Tune': The Daily Express, family and evacuation in 1939. Issue 3 (2nd October 2017) - Dale, Caroline
Abstract : This article investigates the portrayal of evacuation in the Daily Express during the Second World War, in particular it will analyse how the Daily Express 's coverage of evacuation represented the family. It addresses the ways in which family are presented in the evacuation stories and the extent to which this developed and changed over time by conducting the first in-depth quantitative analysis of the Express content in wartime. There is a central enigma at the heart of the Express 's evacuation coverage, and it requires greater investigation. How did a popular newspaper, which defined itself as a 'family friendly newspaper', discuss a scheme which intrinsically broke up 'normal' family life? While the Evacuation Scheme broke up individual families, thereby changing a central aspect of British society, it ultimately sought to create a new type of 'family' in its place, with new foster families taking on the role of 'temporary parents', providing familial continuity and stability for children in the countryside. Ultimately, the Daily Express wanted to be useful to its readers and help them adapt to their new wartime lives, however, its image of 'new families' in the newspaper was based upon a traditional, more conservative, image of family life in wartime. Men and women occupied traditional roles within the family unit, with the images and ideas regarding family used to reassure the Express 's readership, demonstrating that particular social values were constant despite wartime difficulties. This article demonstrates why it is so important to study newspaper content in detail, showing that the popular press is central to our understanding of wartime life and the contrasting opinions, experiences and ideas which characterised British society in 1939.